Femmes téléphonistes et employées des chèques postaux aux PTT : une stratégie syndicale de mise en visibilité des atteintes à la santé au travail (1950-1960) - Bruno Mahouche (La Nouvelle Revue du Travail)
The article covers issues arising during efforts to increase the visibility of the connection between work, on one hand, and damage to the mental health of female French Post Office telephone workers and cheque service employees. Scientific analysis of work-related risks in this area starts with a look at the stance taken by Louis Le Guillant, a well-respected medical psychiatrist and Communist activitst. This position was later adopted by CGT union leaders, and subsequently by feminist activists. All of these social agents have had a part to play in the slow maturation of a union narrative revolving around health at work, the goal being to mobilise women working at the bottom of the staff pyramid, who are sometimes reputed to be resistant to the idea of collective action. The article shows how during the 1960s, the Post Office Administration was the stage for a great many social movements, largely due to female telephone and postal cheque service workers’ engagement.